2024
DOI: 10.1111/jbi.14810
|View full text |Cite
|
Sign up to set email alerts
|

Sampling completeness changes perceptions of continental scale climate–species richness relationships in odonates

Fernanda Alves‐Martins,
Juliana Stropp,
Leandro Juen
et al.

Abstract: AimInsects are one of the least studied taxa, with most species lacking basic ecological and biogeographical information. This problem is particularly acute in the tropics, where low sampling effort hampers accurate estimates of species richness at scale and potentially confounds efforts to identify the drivers of biogeographical gradients. Here, we evaluate the quality of the data on the distribution and diversity of odonate species in the Neotropics, while also examining the influence of sampling completenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
1
1
0
Order By: Relevance
“…Despite covering only Our results showed that the current knowledge on the Odonata fauna covered less than 2% of the grid cells of the Pampas (Figure 1). These results featured the huge spatial knowledge gap on the odonate fauna in this biome, despite the steady increase in the amount of scientific research published on Odonata in the last decades, especially in Brazil and Argentina (Lozano et al, 2020;Miguel et al, 2017;Muzón et al, 2023;Oliveira-Júnior et al, 2022), and agree with reviews describing the current lack of data on the distribution of Neotropical Odonata (Alves-Martins et al, 2024;Beatty et al, 2022). This result is similar to the shortfall in tropical forests-a previous study showed that mayfly distribution covered less than <5% of the range of the Brazilian Amazon territory (Cardoso et al, 2023).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Despite covering only Our results showed that the current knowledge on the Odonata fauna covered less than 2% of the grid cells of the Pampas (Figure 1). These results featured the huge spatial knowledge gap on the odonate fauna in this biome, despite the steady increase in the amount of scientific research published on Odonata in the last decades, especially in Brazil and Argentina (Lozano et al, 2020;Miguel et al, 2017;Muzón et al, 2023;Oliveira-Júnior et al, 2022), and agree with reviews describing the current lack of data on the distribution of Neotropical Odonata (Alves-Martins et al, 2024;Beatty et al, 2022). This result is similar to the shortfall in tropical forests-a previous study showed that mayfly distribution covered less than <5% of the range of the Brazilian Amazon territory (Cardoso et al, 2023).…”
Section: Discussionsupporting
confidence: 82%
“…Although Odonata is one of the most taxonomically well-resolved insect orders, with a sharp increase in the number of species descriptions recently (particularly in the Neotropics), estimates suggest that $500 Odonata species remain to be described in the world (Olaya, 2019;Parise Pinto et al, 2022). Nevertheless, significant knowledge gaps regarding biology and distribution of the order remain in the Neotropical region (Alves-Martins et al, 2024;Beatty et al, 2022). Although the number of odonate species listed as threatened in the IUCN red list continues to increase, conservation assessments of Neotropical aquatic insects are scarce (Sánchez-Bayo & Wyckhuys, 2019).…”
mentioning
confidence: 99%